RANCANG BANGUN APLIKASI KOMUNITAS MENDONGENG BERBASIS ANDROID - Agus Wisnu Kusuma Nata; I Made Arsa Suyadnya; Duman Care Khrisne (Jurnal SPEKTRUM, 2022)
The culture of giving fairy tales to children has an important role in the development oftheir thinking patterns. This culture is starting to be abandoned and wants to be preserved againby the Bali Storytelling community. The community regularly holds or fills an event withstorytelling activities. This study designs and builds an android-based mobile application for thestorytelling community in managing community information such as managing information onstorytelling activities, managing activity participants, managing fairy tale content, recruitingcommunity members, and managing collaboration invitations aimed at the storytellingcommunity. The application is built with the Flutter framework as the application frontend andthe Laravel framework as a REST API which acts as an intermediary for data flow betweenapplication and database. The results of the black box test show that the application can run allfunctionality well and the results of the System Usability Scale test, the application gets a scoreof 73,375 which indicates the application is classified as good and can be accepted by the user.